Role of Oxidative Stress in Ocular Diseases Associated with Retinal Ganglion Cells Degeneration - Eugene Yu-Chuan Kang; Pei-Kang Liu; Yao-Tseng Wen; Peter M. J. Quinn; Sarah R. Levi; Nan-Kai Wang; Rong-Kung Tsai (MDPI AG, 2021)
Ocular diseases associated with retinal ganglion cell (RGC) degeneration is the most common neurodegenerative disorder that causes irreversible blindness worldwide. It is characterized by visual field defects and progressive optic nerve atrophy. The underlying pathophysiology and mechanisms of RGC degeneration in several ocular diseases remain largely unknown. RGCs are a population of central nervous system neurons, with their soma located in the retina and long axons that extend through the optic nerve to form distal terminals and connections in the brain. Because of this unique cytoarchitecture and highly compartmentalized energy demand, RGCs are highly mitochondrial-dependent for adenosine triphosphate (ATP) production. Recently, oxidative stress and mitochondrial dysfunction have been found to be the principal mechanisms in RGC degeneration as well as in other neurodegenerative disorders. Here, we review the role of oxidative stress in several ocular diseases associated with RGC degenerations, including glaucoma, hereditary optic atrophy, inflammatory optic neuritis, ischemic optic neuropathy, traumatic optic neuropathy, and drug toxicity. We also review experimental approaches using cell and animal models for research on the underlying mechanisms of RGC degeneration. Lastly, we discuss the application of antioxidants as a potential future therapy for the ocular diseases associated with RGC degenerations.